2013
DOI: 10.1007/128_2012_400
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Lewis Acid and Base Functions: A Generalized View of the Frustrated Lewis Pair Concept with Novel Implications for Reactivity

Abstract: Sterically congested Lewis pairs cannot form Lewis adducts; instead they establish encounter complexes of "frustrated" Lewis pairs (FLPs). These encounter complexes have recently been recognized to be capable of activating, i.e., splitting, homopolar and polar single and double bonds, which rendered a new reactivity principle. With the help of qualitative orbital considerations this chapter reviews and explains the reactivity of FLPs toward homopolar Z-Z or Z-Z' single bonded molecules, such as H-H and C-H sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Recently, we reported that 1,3,2‐diazaphospholene 1 (Scheme ) effectively catalyzes transfer hydrogenation of a NN bond with ammonia–borane 9. The rate‐determining step involves a concerted double‐hydrogen transfer where the electrophilic P atom accepts a hydride ion (H − ) via a six‐membered‐ring transition state (Scheme ) 10. We reasoned that, similar to the cases of highly Lewis acidic boranes,7, 8 the strong electron‐accepting ability of the P atom of 1 may allow for interaction with a σ‐bond of other substrates, presumably leading to the formation of a four‐membered‐ring transition state followed by σ‐bond metathesis, if the pathway is favored thermodynamically.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we reported that 1,3,2‐diazaphospholene 1 (Scheme ) effectively catalyzes transfer hydrogenation of a NN bond with ammonia–borane 9. The rate‐determining step involves a concerted double‐hydrogen transfer where the electrophilic P atom accepts a hydride ion (H − ) via a six‐membered‐ring transition state (Scheme ) 10. We reasoned that, similar to the cases of highly Lewis acidic boranes,7, 8 the strong electron‐accepting ability of the P atom of 1 may allow for interaction with a σ‐bond of other substrates, presumably leading to the formation of a four‐membered‐ring transition state followed by σ‐bond metathesis, if the pathway is favored thermodynamically.…”
Section: Methodsmentioning
confidence: 99%
“…Among the various strategies that are known for MLC, the bond activation can occur across the M–L bond of a Lewis-acidic metal center and an adjacent Lewis-basic ligand. This structural motif can be considered as a transition metal frustrated Lewis pair (FLP) . Complexes with polar metal–nitrogen bonds are the most prominent representatives and have evolved as well-established catalysts in hydrogenation chemistry .…”
Section: Introductionmentioning
confidence: 99%
“…[9] The rate-determining step involves a concerted double-hydrogen transfer where the electrophilic P atom accepts a hydride ion (H À ) via a sixmembered-ring transition state (Scheme 1 f). [10] We reasoned that, similar to the cases of highly Lewis acidic boranes, [7,8] the strong electron-accepting ability of the P atom of 1 may allow for interaction with a s-bond of other substrates, presumably leading to the formation of a four-membered-ring transition state followed by s-bond metathesis, if the pathway is favored thermodynamically. To examine our hypothesis, we employed a hydroboration reaction [11] so as to let an interaction between boron and oxygen atoms in the transition state be involved, expecting the subsequent formation of the strong BÀO bond which could be a driving force to induce the desired metathesis.…”
Section: Metathesishasbeenbroadlyusedasapreferredmethodformentioning
confidence: 99%